How efficient are real estate and construction companies in Iran’s close economy? - Wong, Wai Peng; Gholipour, Hassan Fereidouni; Bazrafshan, Ebrahim (International Journal of Strategic Property Management, 2012)
This paper empirically explores various efficiency aspects of real estate and construction companies in Iran in light of their remarkable growth in recent years. The technique used to measure the efficiency is DEA and the sample is taken from the construction and real estate companies in Iran. Results from our analysis reveal that most of the real estate and construction companies in Iran are generally technical, scale and mix efficient. However, they are less cost efficient due to increasing higher cost of production. The sensitivity analysis results also suggest that the real estate and construction companies are experiencing diseconomies of scale. As Iran is an underdeveloped market and is currently one of the most interesting frontier markets in the world, this research contributes substantially to investors and multinationals (who have growing desire to gain exposure in this market) by providing current information about the efficiencies of real estate and construction companies in Iran. In addition, this research also provides some institutional voids on how to penetrate market environment in Iran through real estate development. First Publish Online: 19 Dec 2012